Female Labour Force Participation and Economic Development: Does the ‘U’ Shaped Hypothesis Hold for West African Countries? - Idowu, Omowumi O. (African Journal of Stability and Development (AJSD), 2023)
Theories show that there is a relationship between female labour participation and economic development, such that as a country transits from informal economy to formal economy, female labour force participation (FLFP) changes. This change and re-organisation of economic activities and the production system have further affected the position of women in the economy. Among the theories for understanding the phenomenon is the ‘U’ shaped hypothesis by Claudin Goldin. This study sourced data from World Bank Data Bank and investigated the validity of ‘U’ shaped hypothesis in 4 selected West African countries based on their gender ratio labour participation ranking. Using fixed effect estimation technique and ‘UTEST’ technique as suggested by Lind and Mehlum (2010), the study discovered that there is no clear evidence of ‘U’ shape in selected West African countries. While there is an inverted ‘U’ shape relationship between FLFP and economic development in Nigeria and Togo, there is no evidence of ‘U’ shape in Ghana and Mauritania. However, analysis on country specific level reveals the peculiarity of each country. This study concludes that there is no ‘U’ shape relationship between female labour force participation and economic development in selected West African countries. It is recommended that governments in West African countries should increase women empowerment and provide family support/child care services for working women.